Antioxidant activities of extracts from five edible mushrooms using different extractants - Boonsong, Suphaphit; Klaypradit, Wanwimol; Wilaipun, Pongtep (Agriculture and Natural Resources, 2016)
Extractions were performed of the total phenolic and flavonoid contents and antioxidant properties of five edible mushroom samplesdLentinus edodes, Volvariella volvacea, Pleurotus eous, Pleurotus sajor-caju and Auricularia auriculardusing three different extractants. Among the three different extractants, 50% (volume per volume; v/v) ethanol was the most suitable for antioxidant extraction from the mushroom samples. The 50% (v/v) ethanolic extract of dried L. edodes contained higher total phenolic and flavonoid contents than in the other mushroom extract samples. The antioxidant activities of 50% (v/v) ethanolic extract of dried L. edodes showed the strongest 2,2-diphenyl-1-picrylhydrazyl radical-scavenging assay (64.34%) compared to butylated hydroxyanisole (BHA) and a-tocopherol at 500 mg/mL. The ethanolic extract showed a lower reducing power of 0.10 compared to BHA and a-tocopherol at 500 mg/mL. Moreover, the L. edodes ethanolic extract also had the highest chelating ability (66.28%) which was lower than for ethylenediaminetetraacetic acid at 500 mg/mL and showed the strongest superoxide radicalscavenging activity (64.17%) compared to BHA and a-tocopherol. Therefore, the 50% (v/v) ethanolic extract of L. edodes could be used as a potential natural antioxidative source or as an ingredient in the fish and fishery product industries.